BECOMING WHOLE AGAIN: THE GOAL OF WOMEN’S STRUGGLE AGAINST SEX ABUSE IN CATHOLIC SCHOOLS IN THE PHILIPPINES - J.A. Cleofas (Acta Theologica)
This article focuses on sex abuse and abuse of power in Catholic schools in the Philippines. I argue that these schools should ground policy design and decision-making on the relational safety model developed by Maria Carmen B. La Viña and her colleagues at the Catholic Safeguarding Institute, and on a holistic pastoral approach developed by Nila Bermisa. The latter offers a life-giving vision on what to aim for in dealing with abuse as Christians, namely renewal and a movement toward fullness of life. I show that failure to reference the work of these two women is connected to the commission of egregious mistakes such as promoting silence and secrecy that further harm victims, partiality toward abusers, perpetuating organisational structures that correlate with abuse, and failing to listen to women who point to a connection between abuse and patriarchal Catholic culture.